Ethics Oversight Practices of the House of Representatives of the Republic of Indonesia - Mahpi, Liansyah; Tanudjaja, Tanudjaja; Oktawila, Denok (WAHANA, 2026)
Enforcing professional ethics in legislative institutions is a fundamental aspect to maintain the dignity, honor, and credibility of the House of Representatives of the Republic of Indonesia (DPR RI). Ethics, philosophically derived from the concept of ethos, encompasses the values, motives, and behaviors that must be adhered to by every member of the council as a representative of the people. This study aims to analyze the authority of the Council Ethics Court (MKD) in enforcing the DPR Code of Ethics and evaluate the effectiveness of its implementation. Using normative juridical research methods, this study utilizes primary, secondary, and tertiary legal materials to assess the institutional structure, mechanisms for handling violations, and the implementation of ethical sanctions against council members. The results show that the MKD has strategic authority to examine, adjudicate, and provide recommendations for sanctions for violations of the code of ethics, ranging from warnings to dismissal. However, the effectiveness of the MKD still faces challenges, particularly related to indications of favoritism, political obstacles, and a lack of proactive initiatives in following up on alleged violations. Optimal oversight requires transparency, independence, and the involvement of external stakeholders to ensure that ethics enforcement is not merely a formality. This study confirms that strengthening the MKD as an instrument of checks and balances is a crucial step to improve the integrity of the legislative body and restore public trust. Consistent implementation of the code of ethics is expected to foster a clean, professional, and accountable political culture within the Indonesian constitutional system.